[Rezension von: McLaughlin, John L., An introduction to Israel's wisdom traditions] - Keefer, Arthur (The journal of theological studies, 2020)
McLaughlin’s Introduction is concise, dense, but not difficult to read, and stays true to its title as an ‘introduction’, containing no side trails or discussions that might distract from the necessities of reading and understanding Israel’s wisdom traditions. The book contains ten core chapters, five of which deal with individual books including Proverbs, Job, Ecclesiastes, Ben Sira, and Wisdom of Solomon. For these, McLaughlin addresses common issues such as structure, authorship, date, and setting, and otherwise takes no uniform approach to the books but instead gives preferential attention to certain features of each: the literary form of Proverbs, the section-by-section content of Job, the themes and units of Ecclesiastes, the topics of Ben Sira, and the interwoven threads within Wisdom of Solomon. His reading is, perhaps, best called broadly diachronic, as editorial and redactional theories are acknowledged but do not guide his discussion.